Antioxidative system in the erythrocytes of preterm neonates with sepsis: the effects of vitamin E supplementation. (September 2014) - Bajčetić, Milica; Otašević, Biljana; Prekajski, Niveska Božinović; Spasić, Snežana; Spasojević, Ivan
Background: Vitamin E is routinely supplemented to preterm babies, including those with neonatal sepsis. Our aim was to examine the effects of neonatal sepsis and vitamin E on antioxidative system (AOS) in the blood. Methods: A prospective, randomized, open label study involved 65 preterm neonates (control/sepsis – 34/31), which were divided into two subgroups – non-supplemented and supplemented with vitamin E (25 IU/day for 60 days). The activities of superoxide dismutase, catalase (CAT), glutathione peroxidase (GPx), and glutathione reductase (GR) were determined in erythrocytes at days 0, 30, and 60, following sepsis diagnosis. Results: There was no difference in the activity of AOS between controls and neonates with ongoing sepsis. At 60 days, septic neonates showed higher CAT activity compared to controls ( P  = 0.027), and lower GPx activity compared to 0 days ( P  = 0.022). The later was mitigated by vitamin E, which on the other hand provoked lower GPx activity at 30 days, compared to untreated septic neonates ( P  = 0.014). In addition, vitamin E suppressed GR activity in septic neonates ( P  = 0.025 and P  = 0.017 at 30 and 60 days). Finally, vitamin E supplementation in control neonates provoked a significant increase of GPx activity ( P  = 0.015 at 60 days). Conclusions: The absence of altered redox settings in the blood of neonates during sepsis episode, and vitamin E-provoked decrease in the activity of some components of AOS, suggest that the supplementation of vitamin E in these patients might not be rational.